2021
DOI: 10.1016/j.sexol.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a marriage checkup with transgender couples

Abstract: This study aims to fill the gaps in relationship wellness intervention research by providing a relationship wellness program, the Marriage Check (MC), to transgender couples. Transgender couples (defined, for this study, as couples where one or both partners self-identify as transgender) may benefit from an MC as a brief prevention program to support relationship health. The research question for this study was: What is the impact of a Marriage Checkup on transgender couples' relationship satisfaction? Researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Relationship therapy can also be an affirming intervention when at least one partner is a TNB individual. In one study of three couples in which all partners were transgender, all three couples demonstrated improved relationship satisfaction after a two-session adaptation of the Marriage Checkup (originally theorized by Cordova 202 ) 203 . A systematic review highlighted seven primary themes in recommendations for family therapy for transgender youths: incorporating psychoeducation; including space for families to process reactions to their family member’s transgender identity; highlighting the protective influence of family acceptance; using several modes of support; providing families with opportunities to be allies and advocates; connecting families to community resources; and attending to contextual factors, such as additional marginalized identities within the family unit 204 .…”
Section: Affirming Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship therapy can also be an affirming intervention when at least one partner is a TNB individual. In one study of three couples in which all partners were transgender, all three couples demonstrated improved relationship satisfaction after a two-session adaptation of the Marriage Checkup (originally theorized by Cordova 202 ) 203 . A systematic review highlighted seven primary themes in recommendations for family therapy for transgender youths: incorporating psychoeducation; including space for families to process reactions to their family member’s transgender identity; highlighting the protective influence of family acceptance; using several modes of support; providing families with opportunities to be allies and advocates; connecting families to community resources; and attending to contextual factors, such as additional marginalized identities within the family unit 204 .…”
Section: Affirming Interventionsmentioning
confidence: 99%
“…Results thus far are promising, but a broader array of psychosocial and psychotherapy interventions for individuals and communities across varying levels of resource access is needed. In addition to individual therapy, data are also needed regarding the process and outcomes of group therapy 201 , 205 207 , relationship therapy 203 and family therapy 204 , 208 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Suatu perkawinan dilangsungkan karena adanya rasa saling percaya satu dengan yang lain maka kebanyakan orang yang akan melangsungkan perkawinan, mereka pada umumnya tidak mempeributkan masalah percampuran harta kekayaan perkawinan. Beberapa penelitian berikut ini membahas tentang perkawinan/pernikahan seperti Chen & van Ours (2020); Dwinopianti (2017); Efevbera & Farmer (2019); Kenny, Koshin, Sulaiman, & Cislaghi (2019); Kern (2010); Kiconco & Nthakomwa (2018); Minten & Dykeman (2020). Perlahan pemikiran masyarakat mulai berubah, para pasangan yang akan melangsungkan perkawinan mulai mempermasalahkan harta kekayaan dalam perkawinan mereka dikarenakan adanya perkembangan jaman dan pengaruh budaya asing.…”
Section: Pendahuluanunclassified
“…Furthermore, a recent RCT found that a subsample of responder couples benefitting from two checkups could maintain most of their improvements across a 5‐year booster session period (Leth‐Nissen et al, 2022 ). Additionally, the MC has been successfully adapted to different populations, for example, low‐income at‐risk couples (Gordon et al, 2019 ), same‐sex couples (Minten & Dykeman, 2019 ), perinatal couples (Darling et al, 2021 ), transgender couples (pilot study by Minten & Dykeman, 2021 ), and military couples (Cigrang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%